COMUNICAÇÃO E MARKETING NA EDUCAÇÃO SUPERIOR: uma análise dos conteúdos comunicacionais online de instituições de ensino privadas - Gasparin, Amanda Vieira Ferrari (2016)
The present marketing context of higher education, where competition is becoming increasingly aggressive, has led education institutions to establish a more strategic and competitive advertising communication management process, seeking to achieve a distinctive position in the competition in order to attract its stakeholders. This work has involved the application of communication objectives in the higher education market, analyzing the ways in which institutions have established communication processes with their target public, directed to the Brazilian private universities. The research is based on literature review, depth interviews with communication and marketing managers from the investigated sector and analysis of the content from online media communication pieces. Initially it was prepared a report about the current context of higher education market in Brazil: its evolution and characterization. Then it was established marketing applied to the higher education sector: concepts and the role assigned to it. Later marketing communication was related to the higher education service and its use in the sector. Then interviews were conducted in-depth - semi-structured, with communication and marketing managers from two institutions located in São Paulo (Insper and Universidade São Judas Tadeu) with opposing positions and different classifications regarding its image to the market - In order to know their views and opinions about the market and marketing communications actions that they have adopted. Finally, content analysis was prepared comparing ads (advertisements) in online media of the two HEI studied. All analysis procedures content have been established and categorized based on communication objectives defined by Yanaze (2011).